A kestrel without hooked beak and talons is not a kestrel for the red-backed shrike (Lanius collurio) - Němec, Michal; Kučerová, Tereza; Veselý, Petr; Fuchs, Roman (Animal cognition, 2021)
Birds are strongly motivated to recognize various predators to secure survival and reproductive success. Thus, predator recognition provides a useful tool for the investigation of the process of discrimination and categorization in non-trained animals. The most important role in this process is usually attributed to the prominent unique features shared by all members within the wider category of predators (sharp teeth or beaks, claws, talons and conspicuous eyes). However, birds are also able to discriminate between particular predator species according to their species-specific features (based mainly on colouration). We manipulated general raptor salient features (hooked beak, talons with claws and eyes with supraorbital ridges) and/or species-specific plumage colouration on the dummy of a Eurasian kestrel (Falco tinnunculus) to investigate their importance in the recognition process of the red-backed shrikes (Lanius collurio) during nest defence. We showed that the presence of general raptor salient features is necessary for the recognition of a predator. The kestrel dummy with natural species-specific colouration with altered raptor salient features was treated by shrikes as a harmless bird. Nevertheless, pronounced changes in colouration also prevented successful recognition of the dummy as a kestrel, even when raptor salient features of a raptor were present.
Keywords: Falconiformes; zobák; Passeriformes; Recognition, Psychology; rozpoznávání (psychologie); Raptors; Animals; Beak; dravci; Nest defence; Colouration; Categorization; zvířata; Discrimination; Salient features